An Analysis of Deixis in the Novel of ‘Ketika Cinta Bertasbih 1’ by Habiburrahman El-Shirazy (Language Circle: Journal of Language and Literature, 2021)
This study was aimed to describe the deixis usage in the novel of Ketika Cinta Bertasbih 1 by Habiburrahman El-Shirazy. Theoretically, this study is expected to be useful for the researcher of language and literature, and practically, this research can contribute the importance of understanding and preserving literature through language. The researcher used a qualitative descriptive method to analyze the content. Furthermore, the data collection had been transcribed and grouped based on the characteristic, form, and function that were related to the formulation of the research objectives. Based on the data analysis, this analysis found the usage of all kinds of deixis included person (I, you, they, we, he/she), time (now, tomorrow, later), place (here), discourse (it, that), and social (sir).